Pengaruh Kedaulatan Rakyat Terhadap Hubungan Dewan Perwakilan Rakyat Daerah Dengan Badan Pemeriksa Keuangan - Agmalun Hasugian; Nam Rumkel; Irham Rosyidi (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2021)
This research focuses on the implementation of people’s sovereignty in the 1945 Constitution of the Republic of Indonesia and its implementation in the working relationship of the Supreme Audit Agency (BPK) and the Regional People's Representative Council (DPRD). The research problem raised is how people's sovereignty affects the relationship between DPRD and BPK and what are the relationships between the two institutions that are influenced by people's sovereignty. To reveal the research problem, normative legal research is used which prioritizes secondary data with two approaches, namely the legal approach and the conceptual approach. The results of the study show that the people's sovereignty in the constitution is realized through one of its principles, namely accountability. Accountability is the embodiment of people's sovereignty as a form of accountability to the people as the giver of the mandate. This principle also underlies the relationship between the DPRD and the BPK which independently has the authority to implement accountability. The relationship between the two institutions is the implementation of accountability in the horizontal dimension, namely (1) checks and balances, namely the examination of the BPK to the DPRD and the submission of the report on the results of the examination by the BPK to the DPRD; (2) Form of Follow-up on Examination Results; and (3) DPRD involvement in planning the examination. As well as accountability to the people, both by the BPK and DPRD in the dimension of vertical accountability.